RANCANG BANGUN ALAT UJI PERMEABILITAS BETON - Handoko Sugiharto; Allan Surya; Koeshardiono Wibowo; Wong Foek Tjong (Institute of Research and Community Outreach - Petra Christian University, 2004)
The permeability of concrete to water is an important factor that have an effect to durability of concrete structures having direct contact with water, such as port structures, bridges, and basements. In order to identify the permeability nature of concrete, permeability testing is needed. This paper presents a concrete permeability test equipment that was designed and built by the authors. The equipment can be used to conduct permeability tests by flow test as well as by penetration test method. The trial tests of the equipment by flow test method were conducted to 12 concrete speciments with water-cement ratio 0.4 and 0.5 and with wet and dry curing method. The averages of coefficients of permeability obtained differ in the range of 5%-26% from that obtained by using permeability test equipment made by Marui. In addition, the trial tests by penetration method were also conducted to six dry-cured concrete speciments with water-cement ratio 0.4 and 0.5. The averages of coefficients of permeability obtained from the penetration test differs from the flow test 23% and 90% for concrete of water –cement ratio 0.4 and 0.5, respectively. Abstract in Bahasa Indonesia : Permeabilitas beton terhadap air merupakan faktor penting yang mempengaruhi durabilitas struktur beton yang berhubungan langsung dengan air, seperti pelabuhan, jembatan, dan basement. Untuk mengetahui karakteristik permeabilitas beton diperlukan uji permeabilitas. Makalah ini menyajikan suatu alat uji permeabilitas beton terhadap air yang dirancang dan dibuat oleh penulis. Dengan alat ini uji permeabilitas beton dapat dilakukan baik dengan cara aliran maupun cara penetrasi. Ujicoba penggunaan alat ini dilakukan dengan cara uji aliran terhadap 12 sampel beton dengan variasi faktor air semen 0.4 dan 0.5 serta variasi curing kering dan basah. Rata-rata koefisien permeabilitas yang diperoleh berbeda sekitar 5%-26% dari yang didapatkan dengan alat uji permeabilitas buatan Marui. Dilakukan pula ujicoba dengan cara penetrasi terhadap enam sampel beton curing kering dengan variasi faktor air semen 0.4 dan 0.5. Rata-rata koefisien permeabilitas yang dari uji penetrasi berbeda dari yang dihasilkan dengan uji aliran masing-masing 23% dan 90% untuk beton dengan faktor air semen 0.4 dan 0.5.